Physical parameters identification for a prototype of active magnetic bearing system - Perea Fabián, Carlos Antonio (2017)
In this thesis the algorithms and strategies for active magnetic bearing should be analysed, implemented and simulated in Matlab as well as experimentally tested in the real-time computation system for a prototype of active magnetic bearing. Develop a general method and algorithm identi cation for active magnetic bearings prototype and get real system parameters that allow generate the equation of state of the system to control its further development. The specific objectives in this Thesis are: Develop a data acquisition system for the AMBs. Analyse the mathematical model of the system from the real system. Conduct experiments of a physical model for data collection. Develop an identification algorithm for the parameters of the real AMBs. Validate system developed by testing the prototype.